Corporate governance practices of banks in developed countries after the financial crisis of 2008. (23rd September 2019) - Ayadi, Nesrine
This paper suggests a classification of 30 banks of four member countries of the euro zone, according to their governance practices, through a principal component analysis. The governance convergence mechanisms of the 30 banks in four countries in 2009 were analysed on the basis of a consistent measurement with this approach. Bringing banks together according to the directors' compensation seems more appropriate to identify the similarities in the behaviour. This will lead us to classify banks into three categories: the first consists of the banks that award a very high incentive pay to their CEO, the second group provides a high compensation to the CEO and the third category gives a relatively low compensation to their CEO.